Deskripsi Kemampuan Sikap Melalui Pendekatan Saintifik Berbasis Scaffolding Pada Pokok Bahasan Alat Optik - suci prihatiningtyas (Universitas KH. A. Wahab Hasbullah, 2019)
The research aims to teach students the scientific attitude skills after learning through a Scaffolding-based scientific approach to optical instrument material. In this study attitude assessment comes from the results of the assessment through observation techniques conducted by observers (teachers) and self-assessment (students). The instrument used is in the form of a rating scale accompanied by rubik. The average attitude of the students for the three meetings included good categories. They have been able to be responsible, work together, have curiosity, care for others. Based on these results it can be concluded that after learning by using a scaffolding-based scientific approach, the results of the assessment of students' attitudes include good categories. Keywords: scientific attitude, scientific approach, scaffolding.